2009
DOI: 10.5688/aj730107
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating an Immunization Certificate Program into the Pharmacy Curriculum

Abstract: Objective. To describe the method of incorporating an immunization certificate training program, such as the American Pharmacists Association's (APhA) Pharmacy-Based Immunization Delivery into a pharmacy curriculum. Design. The program was delivered over 3 weeks in the spring semester of the third professional year (P3) as part of a required Pharmacy Care Lab sequence. Assessment. Student response surveys and faculty input were used to evaluate the placement of the program in the curriculum. Conclusion. Option… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…The program was delivered over 3 weeks in the spring semester of the third professional year (P3) as part of a required Pharmacy Care Lab sequence. The study found that more than 44% of students provided positive feedback regarding the course with about 10% reporting that the course should not be mandated in the curriculum 5. This study is limited by the fact that it was completely qualitative in nature and did not extensively evaluate the program.…”
Section: Introductionmentioning
confidence: 95%
“…The program was delivered over 3 weeks in the spring semester of the third professional year (P3) as part of a required Pharmacy Care Lab sequence. The study found that more than 44% of students provided positive feedback regarding the course with about 10% reporting that the course should not be mandated in the curriculum 5. This study is limited by the fact that it was completely qualitative in nature and did not extensively evaluate the program.…”
Section: Introductionmentioning
confidence: 95%
“…The first formal national training and certificate program aimed at pharmacists was introduced by the American Pharmacists Association in 1996 and was quickly adopted as a curricular model and component by many colleges and schools. [1][2][3] The 1990s also saw extensive changes to many pharmacy practice acts, expanding the pharmacists' scope of practice to include the administration of immunizations. By 2004, forty-three states recognized pharmacists as immunizers, and now all 50 states, including the District of Columbia and Puerto Rico, have authorized such privileges.…”
mentioning
confidence: 99%
“…A contemporary example of this disconnect might have been evident in the late 1990s when smaller numbers of colleges and schools first began formally incorporating training regarding the delivery of pharmacy-based immunizations. 21,22 At the time, very few state boards of pharmacy had modernized practice acts in order to allow pharmacists to actually administer vaccines, and even fewer pharmacies and pharmacy corporations expressed interest in this clinical service. It was difficult for many to envision the current scope of pharmacy-based immunization services in the United States, with every state now granting pharmacists the privilege of administering immunizations.…”
Section: A Curriculum Designed To Prepare For the Professionmentioning
confidence: 99%